KATA GANTI ORANG DALAM NOVEL THE STARS SHINE DOWN KARYA SIDNEY SHELDON - BERGMANN, STEPHANY (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2015)
ABSTRACT The title of this research is â€œPersonal Pronouns in The Novel The Stars Shine Down By Sidney Sheldon â€. The objectives of this research are to identify, to collect and to analyze the form of personal pronouns in the novel. The data are collected by focusing on the use personal pronouns by the author of the novel. The problem of the research is : what are the personal pronouns in term of form and function in the novel The Stars Shine Down By Sidney Sheldon. I, she, we, they, can be subjects of a verb. Example : I saw it. He knows you. They live near here. Complements of the verb to be : Example : It is I. Me, him, her, us, them can be direct objects of a verb : Example : I saw her. Tom likes them. Those concepts above will be used for identifying and analyzing data. The result shows that the forms of personal pronouns in the novel The Stars Shine Down By Sidney Sheldon are in singular and plural forms. In terms of the function, there are personal pronouns that have the function as a subject, object, possessive adjective and possessive pronoun in the sentences. Â  Keywords: Personal Pronouns in the novel The Stars Shine Down by SidneyÂ  Sheldon, Contrastive Analysis.